2021
DOI: 10.3390/polym13142354
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of Cell-Laden Gelatin Methacryloyl Hydrogels with Incorporation of Silanized Hydroxyapatite by Visible Light Projection

Abstract: Gelatin methacryloyl (GelMA) hydrogel is a photopolymerizable biomaterial widely used for three-dimensional (3D) cell culture due to its high biocompatibility. However, the drawback of GelMA hydrogel is its poor mechanical properties, which may compromise the feasibility of biofabrication techniques. In this study, a cell-laden GelMA composite hydrogel with a combination incorporating silanized hydroxyapatite (Si-HAp) and a simple and harmless visible light crosslinking system for this hydrogel were developed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Hydroxyapatite (HA) is a biomimetic calcium phosphate ceramic material with a chemical composition similar to that of natural apatite found in natural bones and teeth. Natural apatite is the main inorganic component of natural bones and teeth, 124,125 which accounts for about 65% and 95%, respectively. As a result, HA has been extensively studying in the field of bone scaffold development.…”
Section: Progress On Vpp-am Of Bioactive Ceramic Bone Scaffoldsmentioning
confidence: 99%
“…Hydroxyapatite (HA) is a biomimetic calcium phosphate ceramic material with a chemical composition similar to that of natural apatite found in natural bones and teeth. Natural apatite is the main inorganic component of natural bones and teeth, 124,125 which accounts for about 65% and 95%, respectively. As a result, HA has been extensively studying in the field of bone scaffold development.…”
Section: Progress On Vpp-am Of Bioactive Ceramic Bone Scaffoldsmentioning
confidence: 99%
“…Silanized hydroxyapatite (HAp) as additives were added into the GelMA hydrogel, and C-C double bonds were introduced into HAp by silanization (Figure 4), and the HAp and GelMA were bonded by covalent bonds during the photocrosslinking process, thereby improving the mechanical properties of the hydrogels. 82 Mechanical properties are an essential index to evaluate bioprinting results. The increase in the filler improves the mechanical properties of the hydrogel, and the filler that can produce bonding with the hydrogel such as covalent bonding is better to enhance the stiffness of the hydrogel.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…It has been shown that a higher concentration of HAp in the presence of VEGF enhanced bone regeneration [62], as observed in Figure 6c. Su et al [63] showed that a composite hydrogel based on silanized GelMA/HAp enhanced the mechanical properties of the hydrogel and displayed high biocompatibility for bone tissue engineering. A major limitation of HAp is its poor biodegradation.…”
Section: Inorganics-based Nanomaterialsmentioning
confidence: 99%